Do pathogens reduce genetic diversity of their hosts? Variable effects of sylvatic plague in black‐tailed prairie dogs. Issue 9 (4th March 2013) - Sackett, Loren C.; Collinge, Sharon K.; Martin, Andrew P.
Abstract Introduced diseases can cause dramatic declines in—and even the loss of—natural populations. Extirpations may be followed by low recolonization rates, leading to inbreeding and a loss of genetic variation, with consequences on population viability. Conversely, extirpations may create vacant habitat patches that individuals from multiple source populations can colonize, potentially leading to an influx of variation. We tested these alternative hypotheses by sampling 15 colonies in a prairie dog metapopulation during 7 years that encompassed an outbreak of sylvatic plague, providing the opportunity to monitor genetic diversity before, during and after the outbreak. Analysis of nine microsatellite loci revealed that within the metapopulation, there was no change in diversity. However, within extirpated colonies, patterns varied: In half of the colonies, allelic richness after recovery was less than the preplague conditions, and in the other half, richness was greater than the preplague conditions. Finally, analysis of variation within individuals revealed that prairie dogs present in recolonized colonies had higher heterozygosity than those present before plague. We confirmed plague survivorship in six founders; these individuals had significantly higher heterozygosity than expected by chance. Collectively, our results suggest that high immigration rates can maintain genetic variation at a regional scale despite simultaneous extirpations in spatially proximate populations. Thus, virulent diseases may increase genetic diversity of host populations by creating vacant habitats that allow an influx of genetic diversity. Furthermore, even highly virulent diseases may not eliminate individuals randomly; rather, they may selectively remove the most inbred individuals.